Livestock-Associated Methicillin-Resistant Staphylococcus aureus in Patients Admitted to Kuwait Hospitals in 2016–2017 - Boswihi, Samar S.; Udo, Edet E.; Mathew, Bindu; Noronha, Bobby; Verghese, Tina; Tappa, Sajida B. (Frontiers in Microbiology, 2020)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) have been reported to colonize and cause infections in animals as well as in humans. LA-MRSA isolates have only recently been identified in patients admitted to Kuwait hospitals. This study was conducted to characterize LA-MRSA isolates obtained from patients admitted to Kuwait hospitals. A total of 202 (7.1%) of 2823 MRSA isolates obtained from clinical samples in 2016 and 2017 in 11 public Kuwait hospitals were identified as LA-MRSA. They were characterized using antibiogram, spa typing and DNA microarray for the assignment of clonal complexes and detection of antibiotic resistance and virulence determinants. LA-MRSA identification was based on the molecular definition inferred from DNA microarray. The LA-MRSA isolates consisted of CC96 (N= 31), CC97 (N= 169), and CC398 (N= 2). Isolates belonging to CC96 and CC398 were resistant to erythromycin and clindamycin mediated by erm(A) and erm(C). CC97 isolates were multi-resistant to gentamicin, kanamycin, erythromycin, clindamycin, tetracycline, chloramphenicol, fusidic acid, trimethoprim and ciprofloxacin and harbored aacA-aphD, erm(A), erm(C), msr(A), tet(K), cat, fusC, and dfrS1. In total 35 spa types were identified among the isolates. CC398 isolates consisted of t899 and t034. Ten spa types were identified among CC96 with t11822 (N=13) as the most prevalent. CC97 consisted of 26 spa types with most belonging to t267 (N=73) followed by t359 (N=39). CC398 comprised of CC398-MRSA-IV and CC398-MRSA-V [PVL+]. CC96 belonged to CC96-MRSA-IV and CC96-MRSA-IV [PVL+] Central Asian caMRSA/WA MRSA-119. CC97 consisted of six strains including CC97-MRSA-V [fusC+], CC97-MRSA-IV WA MRSA-54/63, CC97-MRSA-V, CC97-MRSA-[V+fus], CC97-MRSA-[mec VI+fus] and CC97-MRSA [mecV/VT+fus+ccrAB2]. While CC96 and CC97 isolates were identified in 2016 and 2017, CC398 isolates were detected only in 2016. This study identified four LA-MRSA clones among MRSA isolated from patients in Kuwait hospitals in 2016-2017 with CC97-MRSA-V [fusC+] as the dominant clone. The presence of LA-MRSA with different genetic backgrounds suggest their independent acquisition from different sources.